2019
DOI: 10.1002/cctc.201901717
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Hydrosilylation of Olefin/Ketone Catalyzed by Iminobipyridine Fe and Co complexes

Abstract: The chemoselective hydrosilylation of olefins and ketones catalyzed by Fe and Co complexes bearing an iminobipyridine derivative ligand was investigated. The reaction of a 1 : 1 mixture of styrene and acetophenone over the Fe catalyst achieved selective hydrosilylation of acetophenone. In contrast, the corresponding Co complex showed the opposite selectivitystyrene-selective hydrosilylation. The reaction of 3-acetylstyrene with both olefin and ketone moieties in the molecule showed that the Co complex catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…Gas chromatography: Trace DSQ GC Column, split = 50:1, flow = 1.1 ml min −1 constant flow, inlet temperature = 250 C, column temperature = 55 C (held for 1 min), then 15 C min −1 up to 120 C, then 20 C min −1 up to 200 C, and then 15 C min −1 up to 280 C, (held for 5 min). 1 H NMR (400 MHz) and 13 C NMR (100.6 MHz) spectra were recorded on a Bruker Advance spectrometer. The data of NMR were listed in the Supporting Information.…”
Section: Catalysis Hydrosilylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Gas chromatography: Trace DSQ GC Column, split = 50:1, flow = 1.1 ml min −1 constant flow, inlet temperature = 250 C, column temperature = 55 C (held for 1 min), then 15 C min −1 up to 120 C, then 20 C min −1 up to 200 C, and then 15 C min −1 up to 280 C, (held for 5 min). 1 H NMR (400 MHz) and 13 C NMR (100.6 MHz) spectra were recorded on a Bruker Advance spectrometer. The data of NMR were listed in the Supporting Information.…”
Section: Catalysis Hydrosilylationmentioning
confidence: 99%
“…Data are available in article supplementary material: copies of 1 H NMR, 13 C NMR, and the data of single crystal of products.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been engaged in developing base metal complexes with high catalytic activity and have reported that Fe complexes bearing an appropriately substituted 2,2':6'2"-terpyridine [12] or iminobipyridine ligand [13,14] as a pincer ligand showed high catalytic activity for olefin and ketone hydrosilylation. Co complexes bearing an iminobipyridine ligand [15,16] have been reported to catalyze an unprece-dented switchable chemoselective hydrosilylation between olefin and ketone frameworks, showing olefin-selective hydrosilylation under neat conditions and ketone-selective hydrosilylation in a pyridine medium. [15] In general, suitable metals and ligands are required for the synthesis of transition metal complexes with excellent catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Co complexes bearing an iminobipyridine ligand [15,16] have been reported to catalyze an unprece-dented switchable chemoselective hydrosilylation between olefin and ketone frameworks, showing olefin-selective hydrosilylation under neat conditions and ketone-selective hydrosilylation in a pyridine medium. [15] In general, suitable metals and ligands are required for the synthesis of transition metal complexes with excellent catalytic activity. In most cases, suitable ligands are not commercially available; therefore, they should be synthesized independently.…”
Section: Introductionmentioning
confidence: 99%